Nanoplastics: From model materials to colloidal fate. (February 2022) - Reynaud, Stephanie; Aynard, Antoine; Grassl, Bruno; Gigault, Julien
Abstract: Nanoplastics are pieces of plastic debris of mixed shape and chemical composition, which can be present in the air, soil, freshwater bodies, seas, biota, and our diet. We know little about the prevalence of nanoplastics and the risks they pose to the health of living organisms; recent studies of plastics in the environment have not significantly contributed information about this crucial topic. In this article, nanoplastics are presented as colloids. Analysing their colloidal properties shows that their fate is governed by interfacial properties, Trojan horse properties, and their stability in aqueous media. Their hazards, however, are as yet unknown. Graphical abstract: Image 1 Highlights: A definition and model material for nanoplastics. Factors that govern the "Trojan horse properties" of nanoplastics. Why nanoplastics need to be considered with all their colloid characteristics? What drives nanoplastic stability and aggregation?